2010
DOI: 10.1063/1.3505800
|View full text |Cite
|
Sign up to set email alerts
|

Structure, magnetic, and thermal properties of Nd1−xLaxCrO3 (≤x≤1.0)

Abstract: Perovskite-type Nd 1−x La x CrO 3 (0 ≤ x ≤1.0) polycrystalline samples were synthesized using solid state reaction. Structural studies indicate that the lattice parameters, metal-oxygen bond lengths, and angles of Nd 1−x La x CrO 3 strongly depend on the La content. Two magnetic transition temperatures, Cr 3+ antiferromagnetic ordering temperature (T N ) and the spin reorientation phase transition temperature (T SRPT ), have been observed in the M-T curves. The increase in T N and decrease in T SRPT with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 42 publications
(34 reference statements)
8
26
0
Order By: Relevance
“…In order to elucidate the microscopic origins of the magnetoelectric coupling in these systems, there have been a number of investigations on the response of various multiferroic materials under different types of perturbations 6,7,8,9 . Within this broad field of study, chemical doping has been used effectively as a tool to study how the structural, magnetic, and electrical properties of multiferroics are affected by small changes in composition 10,11,12 . Doping studies have also been used to explore how the multiferroic ordering temperature changes and microscopic magnetic interactions that give rise to the multiferroic behavior are affected under perturbations, providing insight into the stability of the magnetic interactions 12,13,14,15 .…”
mentioning
confidence: 99%
“…In order to elucidate the microscopic origins of the magnetoelectric coupling in these systems, there have been a number of investigations on the response of various multiferroic materials under different types of perturbations 6,7,8,9 . Within this broad field of study, chemical doping has been used effectively as a tool to study how the structural, magnetic, and electrical properties of multiferroics are affected by small changes in composition 10,11,12 . Doping studies have also been used to explore how the multiferroic ordering temperature changes and microscopic magnetic interactions that give rise to the multiferroic behavior are affected under perturbations, providing insight into the stability of the magnetic interactions 12,13,14,15 .…”
mentioning
confidence: 99%
“…Whereas the magnetization in LaFeO 3 is only due to the FeeFe interaction. Moreover, substitution of La 3þ ions by Pr 3þ ions results in a smaller unit cell volume, larger in-plane FeeO bond lengths, and a greater out-of-plane tilting of FeeOeFe bond, which in turn decreases the transition temperature T N [45].…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…Substitution of Nd by La is reported to increase T N value but reduce T SRT [11]. Troyanchuk et al [12] have reported magnetization reversal in NdMn 0.15 Cr 0.85 O 3 compound below 150 K. Even though, there are several reports on the study of sign reversal of magnetization in LaCrO 3 -based system by carrying out substitutions either at La site or at Cr sit [2][3][4] but such reports on NdCrO 3 system is limited.…”
Section: Introductionmentioning
confidence: 95%